2015
DOI: 10.1590/0101-60830000000042
|View full text |Cite
|
Sign up to set email alerts
|

Associations between chronic pelvic pain and psychiatric disorders and symptoms

Abstract: Background: Chronic pelvic pain (CPP) is a complex condition wich is associated with emotional factors, specially depression and anxiety. Objectives: To make a systematic review to provide a detailed summary of relevant literature on the association between CPP and different psychiatric disorders/symptoms. Methods: A systematic review of articles in the international literature published between 2003 and 2014 was performed in the electronic databases PubMed, PsycINFO, LILACS, and SciELO using the terms (chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…These results are consistent with studies which have suggested that women with CPP conditions have higher rates of depression and anxiety in comparison to general population samples. 10,17 Depression Depression was found to be higher in participants with increased pain severity, presence of stabbing pain, pain as a child and a prior experience of distressing sexual events. The findings support the results of Yosef et al 24 who found that increased depression scores on the PHQ-9 were associated with higher pain severity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results are consistent with studies which have suggested that women with CPP conditions have higher rates of depression and anxiety in comparison to general population samples. 10,17 Depression Depression was found to be higher in participants with increased pain severity, presence of stabbing pain, pain as a child and a prior experience of distressing sexual events. The findings support the results of Yosef et al 24 who found that increased depression scores on the PHQ-9 were associated with higher pain severity.…”
Section: Discussionmentioning
confidence: 98%
“…[12][13][14][15][16] Furthermore, CPP has been shown to significantly impact on this psychological well-being of women, with elevated distress, hopelessness, depression, anxiety seen across CPP samples in the research literature. 4,7,9,10,12,15,17 Despite the demonstrated psychological impact of CPP, there is no strong evidence to advocate the use of psychological interventions as an adjunct to medical intervention for women with these conditions. This is concerning, as psychological interventions may have the potential to manage and treat the CPP related concerns.…”
Section: Introductionmentioning
confidence: 99%
“…The main results in the current study pointed out significant differences in the prevalence of current Major Depressive Episodes between women with and without CPP. The recent review conducted by Carvalho et al[ 11 ] highlighted the link between depressive symptomatology and CPP. However, the present study advanced in the knowledge about this association since it used the gold standard diagnostic interview and a control group paired by age, school level and economic status to assess the presence of depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, these authors state that the associations between sexual abuse and CPP are more prevalent in low methodological quality studies; thus, it is worth being careful at the time to interpret the results. There are also evidences about the association between depression and anxiety symptoms, and CPP[ 11 ]. Nevertheless, one of the weakest points to these evidences is the quality of the studies, most of them are descriptive and just assess the symptoms rather than confirming the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis-associated infertility has negative impacts on both marital relationships and social activities (15). Painful sex and sexual dysfunction (consequences of endometriosis) also negatively affect the quality of life, marital relationships and self-confidence leading to development of mental disorders including depression, anxiety, mood disorders and mental diseases (16,17). Other endometriosis-associated symptoms including dysuria, dysmenorrhea, dyspareunia, and pelvic pain reduce mental health of the patients (18,19).…”
mentioning
confidence: 99%